Augustan sword-scabbards with net-like fitments - Istenič, Janka (Arheološki vestnik, 2003)
The paper deals with net-like fitments which were attachedto the tips of sword-scabbards. In two cases it is clear thatsuch fitments were attached to scabbards of the Mainz type.The relatively good dating evidence indicates that they werecurrent during the time of Augustus, especially in the decadesbefore Christ. Their wide geographical distribution implies thatthey were part of the “regular” production of Roman weapons.Their chronological relationship to the openwork/opus interrasileand embossed fitments, which also occurred on sword-scabbardsof the Mainz type, is discussed as well